Sacrificial offerings: the exercise of power by institutions - Fallon, Finian (Leitura Flutuante, 2012)
This paper explores the manner in which institutions often appear willing to sacrifice individual rights in order to maintain the integrity of the organisation, in spite of the obvious suffering of the petitioner. It explores a psychoanalytic rationale for why servants of exemplars such as state organisation are so willing to participate in the sacrifice of common sense and fairness in protecting institutions, almost at all costs. The author uses a Lacanian lense to reflect on the historic relationship between master and subject to delineate the contemporary roles of official and service user and considers how the resulting dynamics are repetitive in nature and often contrary to ethical perspectives. The paper explores the shock of individuals when they encounter mistreatment at the hands of officialdom while also exploring the factors which push petitionees into rigid and punitive positions in defence of the organisation. About the Author: Finian Fallon is an accredited psychotherapist working in Ireland. He holds a Masters in Addiction Studies and is currently completing a Doctorate in Psychotherapy at Dublin City University. He also lectures in psychotherapy.